Academic Debt in Higher Education: An Analysis of the Causes and Opportunities to Overcome - Yu. S. Ezrokh; A. M. Kashirina (Высшее образование в России, 2023)
Academic debt can cause a significant damage to the Russian economics and the higher education system in the medium term (on the horizon of 5–10 years). The purpose of the study is to identify the key problems based on the results of a comprehensive empirical analysis of the situation of the formation of massive academic debt (using the example of the “Business Informatics” direction at a Russian university) and to substantiate ways to improve the activities of universities in order to overcome them and reduce students’ academic dept. Research methods are general scientific (deduction, induction, generalization, comparative analysis, etc.), as well as special ones (correlation and regression, statistical, sociological surveys, etc.). Analytics and visualization of quantitative data were carried out using MS PowerBI software. Research results. It was revealed that: a) high incoming scores do not guarantee trouble-free education at the university; b) students with low scores (but not less than 160–170) are also able to master quite complicated university programs; c) the presence of academic debts does not depend on the type of disciplines studied (economics / information technology). The number of student dropouts in the studied sample (up to 50% of those who entered with a non-linear dependence on the total USE scores) testifies to the presence of reasons that are not related to the incoming educational potential of students. The results of the study made it possible to structure them into three groups: insufficient motivation, self-organization problems, and “incomplete maturation”. Five groups of students have been identified with an increased risk of accumulating academic debt. The article substantiates the use of indirect educational influence on the students through a special mobile application.